Between Local Belief and International Norms: Gender Inequality among Marapu Women in Sumba - Aristeus, Syprianus; Firdaus; Utami, Penny Naluria; Shahrullah, Rina Shahriyani; Baskoro, Aji; Saadah, Chuzaimatus (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2025)
Although Indonesia’s legal framework recognizes indigenous religions and upholds gender equality, these principles remain largely unrealized for Marapu women due to the intersection of patriarchal customary systems and state institutional biases. This study explores the persistence of gender inequality among Marapu women.  Employing an empirical socio-legal approach, data were collected through literature review and field research, including in-depth interviews and observations across four regencies of Sumba Island: East, Central, West, and Southwest Sumba. Informants included representatives from government agencies, NGOs, and Marapu community leaders. Findings indicate that while Marapu cosmology symbolically recognizes gender dualism, its social practice sustains male authority in ritual leadership, inheritance, and decision-making. State institutions, through religious and administrative structures, indirectly perpetuate these inequalities by privileging formal religions and patriarchal norms. The study concludes that promoting gender justice for Marapu women requires contextual reforms that integrate cultural reinterpretation, community participation, and inclusive policy frameworks grounded in feminist legal pluralism. [Meskipun kerangka hukum Indonesia telah mengakui keberadaan agama-agama leluhur serta menegaskan prinsip kesetaraan gender, realitasnya prinsip tersebut belum sepenuhnya terwujud bagi perempuan Marapu. Hal ini disebabkan oleh persinggungan antara sistem adat yang patriarkal dengan bias kelembagaan negara yang turut memperkuat posisi subordinat perempuan. Penelitian ini mengkaji ketimpangan gender yang dialami oleh perempuan Marapu penghayat kepercayaan di Sumba. Data diperoleh melalui studi pustaka dan penelitian lapangan yang mencakup wawancara mendalam serta observasi di empat kabupaten di Pulau Sumba: Sumba Timur, Sumba Tengah, Sumba Barat, dan Sumba Barat Daya. Informan terdiri atas perwakilan lembaga pemerintah, organisasi non-pemerintah, serta tokoh dan pemimpin komunitas Marapu. Hasil penelitian menunjukkan bahwa meskipun kosmologi Marapu secara simbolik mengakui dualisme gender, praktik sosialnya tetap mempertahankan dominasi laki-laki dalam kepemimpinan ritual, hak waris, dan pengambilan keputusan. Sementara itu, institusi negara melalui struktur keagamaan dan administrasi turut memperkuat ketimpangan ini dengan memprioritaskan agama formal dan norma patriarkal. Hasil temuan penelitian menunjukkan bahwa keadilan gender bagi perempuan Marapu memerlukan reformasi kontekstual melalui reinterpretasi nilai adat, partisipasi komunitas, serta kebijakan inklusif yang berlandaskan pada pluralisme hukum feminis.]